ASPECTS OF THE FORK GLAND (THIMUS) CHILD (PART III) - Юрий Иванович Ровда; Светлана Александровна Шмулевич; Алена Владимировна Ведерникова; Наталья Николаевна Миняйлова; Андрей Владимирович Шабалдин; Сергей Фадеевич Зинчук; Яна Вячеславовна Юнкина; Елена Борисовна Лукоянычева (The Publishing House Medicine and Enlightenment, 2021)
The thymus gland (thymus) is a huge mystery of biology, medicine (primarily immunology) and, in particular, pediatrics. Despite the fact that it has been calling attention of researchers for over 4 centuries. Only in the 20th century, the attitude of scientists to the organ as to a generator and regulator of immune reactions, a participant in the production and differentiation of many populations of immunocompetent cells, and so on, was determined. The thymus is now regarded as a derivative of the immune system and, to a greater extent, as its central organ. Infectious diseases, systemic autoimmune diseases, oncology, the problem of tissue incompatibility determine the life expectancy of a person and therefore the scientific interest to the functions of the immune system and its central organ - the thymus gland is understandable. The key challenge of the study is in the huge number of integral connections of the thymus gland with other components of the immune system, microbiome, neuroendocrine, hematopoietic and connective tissues, organs (and cells) providing barrier function, etc. To isolate functions directly related to the thymus from this continuum is a high-tech task of extreme complexity. The interest of pediatricians in this area of knowledge is associated with a certain understanding of human ontogenesis from birth to old age, where the thymus plays a major role in the antenatal and early postnatal periods. The purpose of this review, as far as possible, is to isolate and focus on some, in our opinion, «white spots» of an ambiguous assessment of morphological transformations and functions attributed to the thymus gland, its structures and cell pool.